Potensi Berwirausaha Mahasiswa Pendidikan Tata Boga Jurusan Ilmu Kesejahteraan Keluarga Universitas Negeri Padang - Nurhasanah, Nurhasanah; Yulastri, Asmar; Fridayati, Lucy (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2016)
This research was motivated by the desire for entrepreneurship education student Catering is high, but in fact are not able to work as an entrepreneur. The purpose of this study was to describe the potential of entrepreneurship education student Catering Department of Family Welfare. This research is descriptive quantitative. The population in the study were all students of Education Catering Padang State University 2010-2012 forces numbering 83 people, and all of them sampled. The data collection technique for potential entrepreneurship using a questionnaire prepared by the